Developing teacher competence in identifying and responding to symptoms of adolescent depression a proposed training program - Rosal, Manol R. (Philippine Journal of Counseling Psychology, 2008)
This study explored the high school students' perception of adolescent depression and the needs of depressed adolescent students as basis for a proposed program to develop the teachers' competence in identifying and initially responding to symptoms of adolescent depression. The investigation was done in three phases: Phase 1, Needs Assessment, utilized focus group discussion (N=40) on high school students' description of a depressed adolescent and the needs of depressed and regular students. Phase 2, based on the result of Phased 1, a prototype program was developed to enhance the teachers' competence in identifying and responding to students who manifest signs of depression. The prototype program was critiqued by three experts in the field of guidance and counseling before it was pilot tested to 26 high school homeroom advisers and guidance counselors from a private college for women in Quezon City, and Phase 3, Development of the Final Program. The data gathered from the evaluation results of the prototype program in Phase 2 were utilized to come up with the final program. The training program was divided into two segments which consisted of the theoretical foundation of adolescent development and adolescent depression, and basic counseling skills for non-counselors and making referrals.